Biological activity of electrochemically synthesized silver doped polyvinyl alcohol/graphene composite hydrogel discs for biomedical applications. (1st November 2016) - Abudabbus, M.M.; Jevremović, I.; Janković, A.; Perić-Grujić, A.; Matić, I.; Vukašinović-Sekulić, M.; Hui, D.; Rhee, K.Y.; Mišković-Stanković, V.
Abstract: Silver/poly(vinyl alcohol), Ag/PVA, and silver/poly(vinyl alcohol)/graphene, Ag/PVA/Gr, composite hydrogel discs were produced by freezing/thawing, followed by electrochemical reduction of Ag + ions inside respective matrices, at constant voltage in specially designed electrochemical cell. Raman, FT-IR and FE-SEM characterized interactions between PVA, graphene and silver nanoparticles. Ag/PVA and Ag/PVA/Gr discs classified as non-cytotoxic towards peripheral blood mononuclear cells (PBMC) according to MTT cytotoxicity test, while exhibiting antibacterial activity against Staphylococcus aureus and Escherichia coli . The slow silver release and high remaining silver content of ∼67–68 wt % after 28 day immersion in simulated body fluid confirmed that both composites can preserve their sterility over time. Highlights: Electrochemical synthesis of Ag/PVA and Ag/PVA/graphene composites. Strong antibacterial activity of composites against S. aureus and E. coli. Composites are non-cytotoxic towards peripheral blood mononuclear cells. High potential of composites for application as antimicrobial medical devices.